Diatoms in the fish rearing center in Temascal, Oaxaca, México - Figueroa-Torres, Ma. Guadalupe (HIDROBIOLÓGICA, 2017)
Considering the importance and lack of studies of freshwater diatoms in Mexico, this research is a contribution to the knowledge of this group, particularly with respect to its taxonomic composition, distribution and abundance in the fish rearing ponds in Temascal, Oaxaca, Mexico. Samples from 14 ponds and two channels (one is supply channel and the other is for draining) were taken in March, 1991. On the whole, 41 samples were obtained which included plankton collected with a 54 µm mesh standard net an a van Dorn bottle, and benthic forms collected with a spatula or a siphon. The diatoms  were cleaned and mounted in Naphrax resin. Relative abundance and frequency were computed counting all the organisms present in one ml of the original smaple, three times. A total of 31 species and varieties of seven families were identified, of which 98% belong to the Pennales order and 2% to the Centrales microcepahal var. microcephala, C. tumida var. tumida, Diploeneis puella var. puella, Gomphonema affine var. affine, G. angustatum var. angustatum, G. clavatum, Navicula notha var. notha y Pinnularia acrosphaeria var. acrosphaeria.